2019
DOI: 10.1002/14651858.cd013160.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose intravesical chemotherapy after nephroureterectomy for upper tract urothelial carcinoma

Abstract: Single-dose intravesical chemotherapy a er nephroureterectomy for upper tract urothelial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Current guidelines recommend a single postoperative instillation of intravesical chemotherapy after RNU, as several trials and meta-analyses showed an approximately 40% relative risk reduction of IVR after administration of a single postoperative dose of intravesical chemotherapy (mitomycin C or pirarubicin) [ 2 , 38 ]. Although we demonstrated that URS prior to RNU is associated with significantly worse IVRFS than RNU alone in patients not receiving immediate intravesical installation following RNU, we were unable to perform subgroup analyses for the subset of patients who received adjuvant intravesical treatment due to a paucity of data.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend a single postoperative instillation of intravesical chemotherapy after RNU, as several trials and meta-analyses showed an approximately 40% relative risk reduction of IVR after administration of a single postoperative dose of intravesical chemotherapy (mitomycin C or pirarubicin) [ 2 , 38 ]. Although we demonstrated that URS prior to RNU is associated with significantly worse IVRFS than RNU alone in patients not receiving immediate intravesical installation following RNU, we were unable to perform subgroup analyses for the subset of patients who received adjuvant intravesical treatment due to a paucity of data.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses have reported lower BRRs in patients receiving intravesical chemotherapy after RNU, and early instillation seems to be of importance as well as single-dose instillation is comparable with multiple instillations [14] , [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Although we demonstrated that URS prior to RNU is associated with significantly worse IVRFS than RNU alone in patients not receiving immediate intravesical installation following RNU or perioperative systemic chemotherapy, we were unable to perform subgroup analyses for populations of patients who received any form of neoadjuvant or adjuvant treatment due to lack of data. Give that single-dose intravesical chemotherapy give for up to postoperative 10 days reduces the risk of IVR within the first post-RNU years and that systemic chemotherapy has a significant beneficial effect on oncological outcomes in patients with UTUC [37,38], further studies including cohorts of patients receiving perioperative chemotherapy are necessary to make preliminary conclusions regarding the impact of URS prior to RNU on IVRFS in such setting.…”
Section: Discussionmentioning
confidence: 99%